Improving Nutrition Information in the Eastern Mediterranean Region: Implementation of Front-Of-Pack Nutrition Labelling - Al-Jawaldeh, A; Rayner, M; Julia, C; Elmadfa, I; Hammerich, A; McColl, K (MDPI, 2020)
The provision of simplified nutrition information, in a prominent place on the front of food packages, is recommended as an important element of comprehensive strategies to tackle the burden of death and disease caused by unhealthy diets. There is growing evidence that front-of-pack nutrition labels are preferred by consumers, are more likely to be looked at or noticed than nutrition labelling on the back or side of packages and can help consumers to better identify healthier and less healthy products. This review summarizes current implementation of front-of-pack nutrition labelling policies in the countries of the WHO Eastern Mediterranean Region. Implementation of front-of-pack nutrition labelling in the Eastern Mediterranean Region remains limited, but three types of scheme were identified as having been implemented or at an advanced stage of development by governments in six countries. Through a review of reviews of existing research and evidence from country implementation, the authors suggest some pointers for implementation for other countries in the Region deciding to implement front-of-pack nutrition labelling policies.